Cooperation in public good games. Calculated or confused? - Goeschl, Timo; Lohse, Johannes (European economic review, 2018)
Some recent experimental papers have claimed that contribution decisions in a public goods game (PGG) are more likely to be cooperative if based on intuition rather than reflection. In light of conflicting findings, this paper (i) reinvestigates the behavioral impact of so-called cognitive style in the PGG; and (ii) connects it with an earlier literature on the role of cognitive failure (confusion). This is motivated by the possibility that the method of time pressure, commonly used to identify cognitive style, invites confusion as a confounding factor. Two channels for such confounds are identified and experimentally tested: A heterogeneous treatment effect of time pressure depending on subjects’ confusion status and a direct impact of time pressure on subjects’ likelihood of being confused. Our reinvestigation of the behavioral impact of time pressure confirms that cognitive style matters, but that deliberation rather than intuition drives cooperation. The confounding effect of confusion is not found to be direct, but to operate through a heterogeneous treatment effect. Time pressure selectively reduces average contributions among those subjects whose contributions can confidently be interpreted as cooperative rather than confused.